Refractive index: a rapid method for determination of starch availability in grains - Sindt, J.J.; Montgomery, Sean P.; Farran, T.B.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Steam-flaked corn samples were used in a series of experiments to determine if refractive index could be used as a rapid, inexpensive method to predict starch availability. Results were best when samples were incubated for 15 min with 500 to 600 active units of enzyme/gm of grain prior to measuring on a hand-held refractometer. Correlations to starch availability determined from gas production by a commercial lab were R=.64 for whole flakes and R=.79 when samples were ground. Samples of corn flaked to different densities produced estimates of solubility similar to an in situ dry matter disappearance assay (R2 = .84, P < .01). Furthermore, refractive index yielded estimates of starch solubility that were well related to a commercial lab’s measures of glucose release for samples of flaked corn that were stored for 0 to 48 hours subsequent to flaking.
Keywords: Beef; Starch availability; Steam-flaked corn; Refractive index